2006
DOI: 10.1002/lsm.20345
|View full text |Cite
|
Sign up to set email alerts
|

Targeted photodynamic therapy

Abstract: Typically there is a modest enhanced accumulation of the PS in tumor tissues, providing a first level of selectivity. Additional selectivity is provided by the confined illumination of the target area with the appropriate wavelength of light. For the treatment of pathologies in complex anatomical sites, such as in the peritoneal cavity, where restricted illumination is difficult; improved targeting of the PS is necessary to prevent damage to the surrounding healthy tissue. This article will focus on targeted P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 61 publications
1
96
0
6
Order By: Relevance
“…It has been reported that PDT damages the microvasculature and induces a vascular shut-down effect (3,12,30). We examined whether induction of vascular endothelial growth factor (VEGF) expression in the LLC/IL-2 tumors may be involved in the enhanced angiogenesis and tumor recurrence following NPe6-PDT.…”
Section: Overexpression Of Il-2 Induced and Promoted Gadd-45αmentioning
confidence: 99%
“…It has been reported that PDT damages the microvasculature and induces a vascular shut-down effect (3,12,30). We examined whether induction of vascular endothelial growth factor (VEGF) expression in the LLC/IL-2 tumors may be involved in the enhanced angiogenesis and tumor recurrence following NPe6-PDT.…”
Section: Overexpression Of Il-2 Induced and Promoted Gadd-45αmentioning
confidence: 99%
“…PDT has the advantage of dual selectivity in that the photosensitizer can be targeted to a destination cell or tissue, and in addition the illumination can be spatially directed to the lesion (7,48). PDT has its origins over a hundred years ago in the discovery of light-mediated killing of microorganisms (35) but since then has been principally developed as a treatment for cancer (8) and age-related macular degeneration (58).…”
mentioning
confidence: 99%
“…В экспериментах H. Solhan et al тестировали эффективность моноклональных анти-EGFR антител, свя-занных с хлорином e6 при различных условиях [48].…”
Section: возможности проведения интраоперационной фотодинамической теunclassified